Evaluation of Crude Protein and Acid-Binding Capacity on Nursery Pig Growth Performance and Fecal Dry Matter - Jessica L. Smallfield; Ron Aldwin S. Navales; Jordan T. Gebhardt; Mike D. Tokach; Jason C. Woodworth; Joel M. DeRouchey; Robert D. Goodband; Katelyn N. Gaffield (Kansas Agricultural Experiment Station Research Reports, 2025)
A total of 360 weanling pigs (DNA 241 × 600; initially 11.5 ± 0.02 lb) were used in a 42-d study to evaluate the effects of crude protein (CP) and acid-binding capacity at a pH of 4 (ABC-4) on nursery pig growth performance and fecal dry matter (DM). Pens of pigs were randomly allotted to one of six dietary treatments in a generalized randomized block design with five pigs per pen and 12 pens per treatment. Pigs were blocked so there were four replications each of light-, medium-, and heavy-weight pens per treatment. Diets were corn-soybean meal-based and arranged in a 2 × 2 + 2 factorial. The first factor, ABC-4, was tested using a low ABC-4 diet formulation concept set at 200 meq/kg and 250 meq/kg in phases 1 and 2, respectively, compared to a traditional formulation concept where the ABC-4 level was not specifically considered. The second factor, CP, was tested at 21% (1.35% SID Lys) and 18% (1.15% SID Lys). Thus, the first four treatment diets consisted of: 1) low ABC-4 at 21% CP, 2) low ABC-4 at 18% CP, 3) traditional ABC-4 formulation strategy at 21% CP, and 4) traditional ABC-4 formulation strategy at 18% CP. Two diets served as controls: 5) treatment 3 with 3,000 ppm and 2,000 ppm of added Zn from zinc oxide (ZnO) in phases 1 and 2, respectively, and 6) treatment 4 with additional feed-grade amino acids (AA) at a SID Lys level of 1.35% while maintaining a CP of 18%. Treatment diets were fed in two phases from d 0 to 7 (phase 1) and d 7 to 21 (phase 2), followed by a common diet from d 21 to 42 (phase 3). On d 7 and 21, fecal samples were collected from the same three randomly selected pigs in each pen to determine fecal DM and fecal scoring. During the experimental period (d 0 to 21), an ABC-4 × CP interaction was observed (P = 0.021), where pigs fed diets formulated to 21% CP had improved feed efficiency (P < 0.001) compared to those fed the 18% CP diets, with the magnitude of improvement being greater when a low ABC-4 diet formulation was utilized. An improvement in ADG, ADFI, and feed efficiency was observed (P ≤ 0.035) when ZnO was added to the traditionally formulated diet at 21% CP. Feed efficiency also improved (P < 0.001) when additional feed-grade AA were added to the traditional 18% CP diet. Overall (d 0 to 42), no ABC-4 × CP interactions were observed. However, pigs previously fed the low ABC-4 diets in phases 1 and 2 had improved (P = 0.009) feed efficiency compared to those fed the traditionally formulated diets. In addition, pigs previously fed 21% CP in phases 1 and 2 had improved (P ≤ 0.004) ADG and feed efficiency compared to pigs fed 18% CP. Similar improvements (P ≤ 0.039) in ADG and feed efficiency were observed when ZnO was added to the traditional 21% CP diet in phases 1 and 2 compared to the same diet without ZnO. Feed efficiency also improved (P = 0.020) in pigs fed the diet with additional feed-grade AA in phases 1 and 2 compared to those fed the traditional 18% CP diet without additional feed-grade AA. For fecal DM, there was an ABC-4 formulation strategy × CP × day interaction (P = 0.043); however, when evaluating ABC-4 × CP interactions on d 7 and d 21, there were no significant interactions within individual days (P ≥ 0.110). Pigs fed low ABC-4 diets had higher fecal DM (P ≤ 0.005) on d 7 and 21 compared to those on traditional diets. On d 7, the 21% CP + ZnO and 18% CP + AA treatments both had higher (P ≤ 0.027) fecal DM compared to their respective treatments of comparison, but these differences were not seen on d 21. On d 21, diets formulated to 18% CP tended to increase (P = 0.052) fecal DM compared to pigs fed 21% CP. In summary, formulating diets using a low ABC-4 concept can improve both growth performance and fecal DM of nursery pigs, and reducing CP to 18% reduced the growth performance compared to 21% CP. Interestingly, formulating to 18% CP with additional AA maintained growth performance at a higher level than expected and warrants further investigation.
Keywords: acid binding capacity; crude protein; fecal dry matter; nursery pig; zinc oxide